Assessment of The Asphalt Produced in Some Factories of Asphalt in Al-Hilla City (Journal of University of Babylon for Engineering Sciences, 2018)
The purpose of this study is to present an evaluation of  the properties and characteristics of asphalt concrete of several hot mix asphalt (HMA) from five factories in Al-Hilla city. The research is divided into two parts. The first part included the laboratory analysis of samples. The second part is evaluation of results according to standard specifications.     The test results included (Asphalt content percent, stability, creep compliance, voids ratio, density, flow, crushed aggregate percent, Loss Angless abrasion and SO3 percent).The results of laboratorial tests indicated that all properties of asphalt mixes were susceptible and possible to be used in the asphaltic roads.The mixes types prepared and tested according to Marshall method. The values of Marshall stability, creep and density are (9.4, 5.4, 9.8, 9, 8.6), (2.5, 2.7, 2.7, 2.6, 2.3) and (2.334, 2.336, 2.337, 2.333, 2.338) with asphalt content between (4.2 to 4.6) % for all asphalt mixes of different factories.